Analysis of Antimicrobial Resistance in Non-typhoidal Salmonella Collected From Pork Retail Outlets and Slaughterhouses in Vietnam Using Whole Genome Sequencing - Holohan, Niamh; Wallat, Maximilian; Hai Yen Luu, Thi; Clark, Eleanor; Truong, Duong Thi Quy; Xuan, Sinh Dang; Vu, Hue Thi Kim; Van Truong, Dung; Tran Huy, Hoang; Nguyen-Viet, Hung; Unger, Fred; Thi Thanh Dang, Son; et al. (Frontiers in Veterinary Science, 2022)
Non-Typhoidal Salmonella (NTS) remains a significant health burden worldwide. In Vietnam, pork accounts for 70% of the total meat consumed and contamination with Salmonella is high. High levels of antimicrobial resistance (AMR) have emerged amongst porcine NTS with particular concern is the emergence of colistin resistance, a ‘last defence’ antibiotic against multi-drug resistant (MDR) Gram-negative pathogens. This study aimed to investigate the antibiotic susceptibility of 69 NTS isolates collected from the pork retail outlets and slaughterhouses in Vietnam during 2014 and 2018/19. Phenotypic testing and whole genome sequencing was used to assess the serotype and AMR gene profiles of the 69 NTS isolates. Seventeen different serotypes were identified, of which S. enterica subsp enterica serotype Typhimurium was the most common followed by S. ser. Rissen, S. ser. London, S. ser. Anatum and S. ser. Derby. Phenotype AMR was common with 41 (59.4%) isolates deemed MDR. MDR strains were most common in slaughterhouses (83%) and supermarkets (75%) and lowest in traditional markets (38%) and convenience stores (40%). Colistin resistance was identified in 18 strains (15 resistant, 3 intermediate) with mcr-1 identified in seven isolates (S. ser. Meleagridis, S. Rissen, S. Derby) and mcr-3 in two isolates (S. Typhimurium). This includes the first mcr positive S. Meleagridis to our knowledge. Surprisingly boutique stores had high levels (60%) of MDR isolates including 5/20 isolates with mcr-1. This study demonstrates that pork from modern retail stores classed as supermarkets or boutique (with pork claiming to be high quality, traceable, environmentally friendly marketed towards higher income consumers) still contained NTS with high levels of AMR.